The roles of muscle contraction and pharmaceuticals on restoring glucose uptake in a mouse skeletal muscle model of immobilization - Kirkpatrick, Euan (2024)
Current understanding of muscle atrophy during immobilization and weightlessness is incomplete, partially due to the barriers to entry in the study of whole muscle. For this reason, a readily available model based on the C2C12 cell line is highly desirable as it would significantly increase the number of researchers able to engage in study of changes to skeletal muscle as a result of inactivity. The work presented here was in part funded as part of a newly established Astropharmacy cohort, which aims to tackle problems facing future manned space exploration. As such, the experiments performed here were planned and analysed with this perspective in mind. Inactivity is known to result in both muscle atrophy and insulin resistance. Terrestrially this is thought to be a key step in the development of diabetes as skeletal muscle is critical for the disposal of glucose during physical activity. For this reason, we are interested in establishing a pharmacological model of immobilisation with associated features including reduced glucose uptake (insulin resistance) and then restoring activity either by EPS (electric pulse stimulation) or further pharmaceutical intervention. Chapter 2 Firstly, we confirmed the suitability of C2C12 cells in our hands as a platform for measurement of glucose uptake using 2-Deoxyglucose (2DG). We determined that at a final concentration of 25µM per well 2-deoxyglucose could be used to trace glucose uptake over a 24-hour period in both the basal and EPS treated state. We confirmed normal cell responses to EPS in terms of anabolic signalling changes, glucose uptake and lactate production. The ability of cells to respond to insulin was also tested and confirmed. Chapter 3 After establishing the suitability of the platform, we were interested in determining the effect of repeated bouts of contraction throughout a 24-hour period effected the endpoints measured previously- glucose uptake, lactate output and anabolic signalling- as well as the addition of cell glycogen content. We found that there were no significant differences in glucose uptake, cell glycogen, lactate output or p-P70 (T389), p-4EBP1 (T37/46), p-mTOR (S2448) at the 24-hour timepoint with any of the frequency/ duration combinations that we attempted. This was attributed to a combination of the lack of a maintenance pulse during the rest periods and possible proximity effect. Chapter 4 Returning to 24-hour continuous EPS we established the ability of combined CPA and blebbistatin (CB) treatment to inhibit contraction in c2c12 cells at concentrations of 100 µM and 10µM respectively. This was paired with increases in biomarkers (ATP2A1 and CALM1) that indicate elevated cytosolic calcium. When treated with EPS the CPA and blebbistatin model showed reduced glucose uptake, reduced P70, ERK1/2 phosphorylation and elevated 4EBP1 phosphorylation compared to cells treated with EPS alone, indicating prevention of contraction and consequent downstream effects in line with immobilisation. Chapter 5 Lastly, we attempted to restore glucose uptake, glycogen, lactate output, anabolic signalling, p EEF2 (T56), p-PKB (T3080), P-ERK1/2 (S217/221) to baseline values by application of combinations of EPS, AICAR and dantrolene. We found that application of these drugs reduced glucose uptake beyond what treatment with CB alone had. However, lactate output and markers of cytosolic calcium improved with dantrolene treatment. In cells that did not receive CB treatment, we found that EPS had a neutral or negative effect in the case of AICAR on the ability of drug treatment to stimulate additional glucose uptake, which may suggest incompatibility between pharmacological and exercise-based uptake methods, possibly due to conflicting signalling between EPS which favours transient changes and drug treatments which favour sustained changes.